Influence of cAMP modulator supplementation of in vitro culture medium on Bos taurus indicus embryos - Costa, Camila Bortoliero; Lunardelli, Paula Alvares; Fontes, Patricia Kubo [UNESP]; Sudano, Mateus José; Gouveia Nogueira, Marcelo Fábio [UNESP]; Alfieri, Amauri Alcindo; Ferreira, Christina Ramires; de Lima, Camila Bruna; Marinho, Luciana Simões Rafagnin; Seneda, Marcelo Marcondes (My University, 2020)
The effectiveness of the use of natriuretic peptide C (NPPC) in the blocking of meiosis has already been proven in several species. However, there are no reports on the use of NPPC in the activation of metabolic processes in embryos. Whereas modulations of cAMP concentrations alter the lipid metabolism of bovine oocytes, the present study aims to evaluate the effect of NPPC on the development, lipid content and transcript levels of genes related to lipid metabolism of IVP bovine embryos. For this purpose, ovaries were obtained from a slaughterhouse, and oocytes were fertilized in vitro (D0). From D5 of in vitro culture, embryos were treated with 100 nM NPPC (NPPC group) or with no NPPC (Control group) and evaluated in terms of Blastocyst (D7) and hatching rates (D10). For the assessment of the cytoplasmatic lipid amounts, blastocysts were stained with Sudan Black B dye. The embryonic lipid profile was investigated by electrospray ionization desorption-mass spectrometry (DESI-MS). The abundance of nine transcripts related to lipid metabolism were assessed using the Biomark HD system. For statistical analysis, blastocyst and hatching rates, lipid content by the Sudan Black B and variation of gene expression between groups were compared by Student t-test. For lipid profile analysis, principal component analysis (PCA) and fold-change were performed. The embryo lipid content was similar between NPPC (881 ± 3.7) and Control (883 ± 5.2) groups (p > 0.05). However, cholesteryl esters and TAGs were downregulated by NPPC at multiple levels according to the DESI-MS profiles. Of the analyzed genes, ELOVL6 and SREBF1 showed an up-regulation in the control group (p < 0.05), while CPT2 was observed to be up-regulated in the NPPC-treated embryos. There was no significant difference in the blastocyst production rate between NPPC (44.4%) and Control (42.4%), however the hatching rate at D10 was higher (p < 0.05) in the NPPC group (69.77%) when compared to the Control group (48.33%). These findings demonstrate that NPPC alters the mRNA expression of genes related to lipid metabolism and that it exerts a positive effect on the hatching rates of IVP Bos taurus indicus embryos.
Keywords: Bovine; Desorption electrospray ionization; Gene expression; IVEP; Lipid content; NPPC